Responding to Banking Crises : Lessons From Cross-Country Evidence - Detragiache, Enrica; Ho, Giang (Washington, D.C. : International Monetary Fund, 2010)
A common legacy of banking crises is a large increase in government debt, as fiscal resources are used to shore up the banking system. Do crisis response strategies that commit more fiscal resources lower the economic costs of crises? Based on evidence from a sample of 40 banking crises we find that the answer is negative. In fact, policies that are riskier for the government budget are associated with worse, not better, post-crisis performance. We also show that parliamentary political systems are more prone to adopt bank rescue measures that are costly for the government budget. We take advantage of this relationship to instrument the policy response, thereby addressing concerns of joint endogeneity. We find no evidence that endogeneity is a source of bias.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet